LEADERSHIP IN LIQUID MODERNITY - Lippi, Julian (The journal of contemporary issues in business and government, 2013)
This paper explores possibilities for refreshing thinking about leadership from perspectives of liquid modernity suggested by Bauman (2000), who identified several dimensions of modern uncertainty in human life and work. Reflecting unease with post-modernism, Bauman’s work has been influential in contemporary understandings of society, culture, learning and identity. It is also being taken up in emerging explorations of liquid learning in the educational literature. However, its implications for leadership remain largely unexplored in the management literature. This paper considers how current conceptions of leadership that emphasise the power of individual agency might be usefully re-considered in the light of Bauman’s contribution and it develops a number of generative questions to help that process. It then turns to conceptions of liquid learning to suggest some navigational aids for leading under conditions of liquidity.